Nutritional knowledge, attitude and practice during pregnancy among antenatal and postnatal mothers in HTAA, Kuantan, Pahang, Malaysia 2016 - Mohd Nasaruddin, Nur Asifa; Ikhsan, Liyana Nabihah; Othman, Farhana; Abd. Aziz, Karimah Hanim; Ismail, Hamizah (2016)
Introduction Balanced and sufficient maternal intake of macronutrients and micronutrients ensures not only the health status of the pregnant mother, wellbeing of the fetus and the newborn but to her future health status. It also cause epigenetic inheritance that carries transgenerational transmission. Good nutritional knowledge may result in good attitude and practice, and they are often correlated with each other. Objectives To assess nutritional knowledge, attitude, and practice and their related factors among antenatal and postnatal mothers in Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang, Malaysia 2016. Methodology A cross sectional study was conducted among 320 antenatal and postnatal mothers who were not on any diet restriction using pre-tested interview-guided questionnaire. Quota sampling was applied. The questionnaire consisted of sociodemographic characteristics, nutritional knowledge, attitude and practice of mothers. Nutritional KAP questions were adapted from several previous studies (Mikyas, 2016; Abgarvan, 2015; Chen, Soo, Ab Rahman, Van Rostenberghe & Harith, 2013; Masuku & Lan, 2014; Parmenter et al.; 2000) Median (IQR) was used in determining cut of point for knowledge, attitude and practice. Descriptive and univariate statistics were used to analyse the data using IBM SPSS version 23.0. Conclusions Slightly more than half of our respondents had good knowledge and practice with almost two-third with good attitude. Being 35 years old and above with higher educational level are significantly related to better nutritional knowledge, meanwhile tertiary education was related to better nutritional practice. Thus our results emphasize on the importance of empowering girls and women with proper educations and to strengthen the nutritional and health education of our educational system. It is for them to be in a knowledgeable state with good attitude and practicing healthy nutritional lifestyle as they enter their reproductive life, maintaining and transferring at least optimum healthy life to their progenies.